Spectral scattering characteristics of subwavelength-sized spherical particles near Mie resonance modes probed by tightly focused Terahertz waves - Da-Hye Choi (Scientific Reports)
Abstract The complex dynamics of terahertz (THz) wave scattering by subwavelength-scale structures remain largely unexplored. This article examines the spectral scattering characteristics of subwavelength-sized spherical particles probed by tightly focused THz waves through numerical simulations and experimental techniques. The simulations reveal that the scattering intensity for lower Mie resonance modes (magnetic dipole and electric dipole modes) remains largely unaffected when THz waves are focused down to 0.3 λ, whereas higher Mie resonance modes experience a significant decrease in intensity as the beam size is reduced. Experimentally, scattering effects were observed by imaging two subwavelength-sized dielectric spheres, each with a diameter of 480 μm and refractive indices of 2 and 6, around 0.3 THz, where the magnetic dipole mode of the particle with refractive index of 2 was detected. Experimental results confirm that the image contrast of the spheres is predominantly influenced by scattering effects near the Mie resonance frequency, even with low refractive index materials. This work represents a significant advancement in the detection and characterization of subwavelength-sized structures within the THz region. Furthermore, the findings extend beyond THz frequency ranges and have potential applications in fields such as sensing, imaging, and sizing across optical, infrared, and millimeter wave ranges.